Job Satisfaction and Work Commitment of Hospitality Industry Employees in Dapitan City - Bureros, Anna Rhea Michelle S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study investigated the relationship between job satisfaction and work commitment among Dapitan City’s hospitality industry employees. It used a descriptive research method utilizing a questionnaire as the principal tool for gathering data. Data were statistically treated using frequency, weighted mean, Mann-Whitney U-Test, Kruskal-Wallis H-Test, and Spearman Rank-Order Correlation. The study revealed that employees were satisfied with their salary (existence), work environment (relatedness), and the way they were mentored in the performance of their jobs (growth). Most of the employees were committed to their work as they identified that the establishment had a deep sense of personal meaning to them (affective); that, for now, choosing to remain in the organization is motivated by both necessity and desire (continuance); and the establishment deserves their loyalty (normative). A significant difference resulted in job satisfaction when analyzed according to civil status. Moreover, when analyzed according to educational attainment and employment status, a significant difference was identified in employees' work commitment. Finally, it was discovered that among hospitality industry employees in Dapitan City, job satisfaction and work commitment have a considerably high positive relationship. Hospitality industry stakeholders and employees are encouraged to support educational advancement and enhance management practices to minimize employee turnover. Legislators and policymakers are encouraged to enact policies and measures in line with the improvement and advancement of hospitality industry employees.